CULINARY TOURISM DEVELOPMENT MODEL IN METRO LAMPUNG CITY - Derinta Entas; Rina Kurniawati; Baskoro Harwindito; Karlina Karlina (Institut Pariwisata dan Bisnis Internasional, 2016)
The purpose of this research is to explore tourism potential in Metro Lampung. The tourism attraction that is potential in Lampung is its local culinary. Culinary tourism is popular nowadays, given the fact that tourists hunt for local food when they are visiting tourist destination. The purpose of this research firstly is to explore the potential of tourism culinary in Metro Lampung City. Secondly is to find the marketing strategy of tourism culinary in Metro Lampung city. Thirdly is to find out the factors needed in promoting local food as tourism attraction in Metro Lampung City.The data is collected from observation, interview, document study, and questionnaires. This research employs descriptive qualitative approach. The is data gathered and analyzed using SWOT analysis. The output of this research is a model design of culinary tourism development. A recommended of tourism development model is community based tourism. Community based tourism model is tourism which concerns on local community with their local wisdom.